Attenuation of metabolic stress response during spinal surgery under general anaesthesia - A comparison between preoperative carbohydrate drink or no carbohydrate load - Arif Hossain; Sangita Mandal; Soumya Chakrabarti; Mohanchandra Mandal; Amita Acharjee (Asian Journal of Medical Sciences, 2022)
Background: Surgery is a stress which stimulates the increase of counter regulatory hormones. Pre-operative prolonged fasting increases stress further. Although a pre-operative carbohydrate (CHO) drink has been variably reported to yield benefit in reducing the perioperative stress and is being used frequently for elective surgeries, some recent reports also reports that preoperative CHO loading did not result in increase or decrease in the post-operative complication rates when compared with placebo or fasting group.